THE DIGITAL MARKETING PRACTICES TOWARDS SMEs PERFORMANCE IN CYBER ENTREPRENEURSHIP - Hazrina Hasbolah; Norazlinda Mohamed Rosdi; Syamsuriana Sidek; Fadhilahanim Aryani Abdullah; Raja Rosnah Raja Daud; Nurul Azwa Mohamed Khadri (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Nowadays, there has been an increasing number of SMEs in the world. SMEs play a vital role in economics across the world and Malaysia particularly. The rapid ICT development in the digital age and pandemic of Covid19 affects many aspects of SMEs performance especially in conducting business and how costumers behave. The use of internet and electronic devices emphasised as an effective tool for running business activities. Parallel to that, incorporating the information and communication technologies (ICT) component into the traditional business and adapting it to the current modes of operation through digital marketing play crucial roles in order to SMEs stay competitive in the marketplace and cope with IR 4.0. Digital marketing has dramatically changed the organization and marketing environment. This study aims to know the relationship between social media and omnichannel marketing toward SMEs’ performance in cyber entrepreneurship in Malaysia. This study was conducted among SMEs across all states in Malaysia that range from the age of 18 years old to 37 years old and above. Besides, this study distributed 370 sets of questionnaires to respondents answering the questions. This study employed a quantitative approach to 370 small businesses comprised of various sectors. The result of the analysis will be obtained through research using Statistical Package for Social Science (SPSS) software for interpreting data. The findings showed that respondent mostly practices digital marketing; social media and omnichannel marketing are significantly connected to SMEs’ performance in cyber entrepreneurship. To help SMEs, compete in the foreseeable challenges of the IR 5.0 era, this present study shines light by alerting the relevant authorities to the necessity of digital marketing in their operation.